Calculating capital requirements for operational risk - Gerd Waschbusch; Sabina Kiszka (Managerial Economics)
Operational risks have become increasingly important for banks, especially against the background of growing IT dependency and the increasing complexity of their activities. Further-more, the corona pandemic contributed to the increased risk potential. Therefore, banks have to back these risks with own funds. There are currently three measurement approaches for determining the capital requirements for operational risk. In recent years, and especially during the Great Financial Crisis of 2007/2008, however, some of the weaknesses inherent in these approaches have become apparent. Thus, the Basel Committee on Banking Supervision revised the current capital framework. Therefore, this article examines the various measurement approaches, addresses inherent weaknesses and moreover, presents the future measurement approach developed by the supervisory authorities.